The use of indocyanine green angiography in arterialized-venous free flaps: Case report and insight into flap vascular physiology. (June 2022) - Gornitsky, Jordan; Beauchemin, Gabriel; Chollet, André; Tremblay, Dominique; Boghossian, Elie
Summary: Arterialized venous flaps (AVFs) are an innovative option in hand reconstruction. Their exact vascular physiology and survival mechanisms remain unclear. We report on two hand reconstruction cases with AVFs. Indocyanine green laser angiography was used to assess vascular perfusion of the flaps. A notable change in flap perfusion was seen by 48 h post-operatively with normalization of shunting and progression to a diffuse perfusion pattern resembling traditional flaps. Flap survival was attributed to reversed shunting at the microvascular level occurring within the first 48 h post-operatively.